Dostoevsky’s Godchildren - Tatiana V. Panyukova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article, based on archival sources, provides new information about two godchildren of F.M. Dostoevsky: Platon Milyukov (with clarification of the name, date and place of his baptism) and Grigoriy Snitkin (the fact of the writer's participation in the baptism has not yet been noted in the biographical literature). Two authentic metric records found in the Central State Archive of Saint Petersburg are put into scientific circulation, allowing to supplement or correct the information contained in the “Chronicle of the life and work” of the writer. The attraction of documentary sources (stored in the Russian State Historical Archive of service and form lists), analysis of the preserved epistolary, reference and biographical literature allowed to attempt to systematize all available data about Grigoriy Ivanovich Snitkin and for the first time to make a biographical reference about his person, native nephew of Anna Grigoryevna Dostoevsky and godson of the writer – thus adding information about F.M. Dostoevsky’s family circle.